Explaining business excellence in Chinese firms: How does institutional relatedness matter? (Chinese Management Studies （SSCI), 2021)
Purpose – It is widely accepted that business excellence comes from firm-specific factors. However, it is still unclear how institutional relatedness – the degree of embeddedness with the dominant institutions that confer resources and legitimacy, influences the business excellence of the firm. The purpose of this study is to explore the influence of three kinds of institutional relatedness, i.e. home government ties, initial public offerings (IPOs) and alliances with foreign firms, on the business excellence of Chinese firms. Design/methodology/approach – This study uses a sample of firms enlisted on the “Most Respected Companies” rank in China during the period 2002–2015 and their paired firms who are absent from the list, by means of ordinary least square regression estimator, to explore the relationship between institutional relatedness and business excellence. Findings – The empirical results suggest that IPOs and alliances with foreign firms significantly strengthen firms’ business excellence. Furthermore, home government ties have positive effects on outbound IPOs and alliances with foreign firms but hinder business excellence. Originality/value – This study extends the business excellence literature by characterizing institutional rather than firm-specific factors from an institution-based view. It also enriches research on outcomes of institutional relatedness through investigating empirically its impact on business excellence. The findings provide new insights into the dual role of home government ties in achieving business excellence.